Functional analysis of rare anti-Müllerian hormone protein-altering variants identified in women with PCOS. (2nd April 2023) - Meng, L; McLuskey, A; Dunaif, A; Visser, J A
Abstract: Recently, rare heterozygous AMH protein-altering variants were identified in women with polycystic ovary syndrome (PCOS), causing reduced anti-Müllerian hormone (AMH) signaling. However, the exact functional mechanism remains unknown. Here, we analyzed the processing, secretion, and signaling of these AMH variants. Functional analysis of six PCOS-specific AMH variants (V 12 G, P 151 S, P 270 S, P 352 S, P 362 S, H 506 Q) and one control-specific variant (A 519 V) was performed in the mouse granulosa cell-line KK-1. Human (h) AMH- 151 S and hAMH- 506 Q have ∼90% decreased AMH signaling compared to wild-type (wt) AMH signaling. Coexpression of hAMH- 151 S or hAMH- 506 Q with wt-hAMH dose-dependently inhibited wt-hAMH signaling. Western blotting revealed that hAMH- 151 S and hAMH- 506 Q proteins were detected in the cell lysate but not in the supernatant. Confocal microscopy showed that HEK293 cells expressing hAMH- 151 S and hAMH- 506 Q had higher cellular AMH protein levels with endoplasmic reticulum (ER) retention compared to cells expressing wt-hAMH. Using two AMH ELISA kits, hAMH- 151 S was detected in the cell lysate, while only very low levels were detected in the supernatant. Both hAMH- 362 S and hAMH- 519 V were detectable using the automated AMH ELISA but showed severely reduced immunoactivity in the manual ELISA. Surprisingly, hAMH- 506 Q was undetectable in both the cell lysate and supernatant using either ELISA. However, in PCOS cases, heterozygous carriers of the P 151 S and H 506 Q variants still had detectable AMH in both assays. Thus, P 151 S and H 506 Q disrupt normal processing and secretion of AMH, causing ER retention. Additionally, AMH variants can impair the AMH immunoactivity. An AMH variant may be considered when serum AMH levels are relatively low in PCOS cases.